Inclusive Education at Makrifatul Ilmi Islamic Boarding School, South Bengkulu - Asiyah Asiyah; Erwin Subly Fadilah; Vina Putri Rahayu (UIN Sunan Gunung Djati Bandung, 2022)
This paper attempts to explain inclusive education at the Makrifatul Ilmi Islamic Boarding School, South Bengkulu. By using content analysis and reflective methods, it was concluded that inclusive education at the Makrifatul Ilmi Islamic boarding school has begun to open itself up to accept students with disability status but still with a simple and limited teaching pattern. This is because there are no special teaching staff for students with disabilities. The seriousness of the Makrifatul Ilmi Islamic Boarding School in accepting students with disabilities is also emphasized by issuing written and unwritten rules so that students respect each other, respect each other and are not allowed to corner anyone, be it gender, ethnicity, race, or physically. persons with disabilities.